2020
DOI: 10.3390/metabo10040132
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Glycolysis Protects against Ischemia-Reperfusion Injury by Reducing ROS Production

Abstract: After myocardial ischemia-reperfusion, fatty acid oxidation shows fast recovery while glucose oxidation rates remain depressed. A metabolic shift aimed at increasing glucose oxidation has shown to be beneficial in models of myocardial ischemia-reperfusion. However, strategies aimed at increasing glucose consumption in the clinic have provided mixed results and have not yet reached routine clinical practice. A better understanding of the mechanisms underlying the protection afforded by increased glucose oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 50 publications
3
30
0
Order By: Relevance
“…Crosstalk between metabolic shift and mitochondrial ROS production was shown recently. Similarly to our work, Beltran et al demonstrated that activation of glycolysis during I/R injury reduced ROS production [20]. The FA β-oxidation also is associated with ROS production.…”
Section: Discussionsupporting
confidence: 90%
“…Crosstalk between metabolic shift and mitochondrial ROS production was shown recently. Similarly to our work, Beltran et al demonstrated that activation of glycolysis during I/R injury reduced ROS production [20]. The FA β-oxidation also is associated with ROS production.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, the ischemia-dependent cardiac contracture starts when glycolysis is interrupted, causing a reduction of ATP that impairs the activity of critical enzymes [ 261 ]. In this context, in animal models of ischemia, cardioprotection has been achieved by increasing glucose and insulin levels, or by raising the use of endogenous glycogen [ 262 , 263 ]. Promising results, in this respect, came from the use of AMPK activators, able to improve cardiac performance recovery and to reduce the infarct size [ 264 , 265 ].…”
Section: Therapeutic Strategies In Cardiac Diseasesmentioning
confidence: 99%
“…8) The mTOR/AKT signalingenhanced glycolysis defends against ischemia/reperfusion injury by decreasing ROS generation. 46) AKT-mediated phosphorylation and activation of PFKFB2 increase glycolysis flux in the heart. 13) Our mechanism study displayed that hypoxia induced the activation of PFKFB2 through HIF-1/ATK signaling in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%